Modal Analysis of Transient Liquid Sloshing in Partially-Filled Tanks - Zheng, Xue Lian; Ren, Yuan Yuan; Cheng, Zhu Qing; Li, Xian Sheng (Applied Mechanics and Materials, 2014)
To investigate the dynamic characteristics of liquid sloshing in partially-filled tanks, FLUENT simulation for liquid sloshing in cylinder tanks with the 40% liquid fill level and subject to lateral accelerations of 0.1 g-0.4 g were carried out. By the observation of transient sloshing force and the liquid free surface, it was found that the liquid sloshing is a periodic oscillation. Fourier transform was utilized to transform the sloshing forces in the time domain to the signals in the frequency domain. By spectrum analysis, it was found that the first-order oscillation that has the biggest amplitude is the most important one for liquid sloshing. For further command on liquid sloshing, modal shapes for the first sixth modal were acquired by ANSYS. It is drawn that the odd modals have anti-symmetrical shapes and the first-order oscillation makes the biggest contribution on liquid sloshing, the even modals have symmetrical shapes and could not contribute to liquid sloshing.